Ironie et communauté (L’Éducation sentimentale) - Boris Lyon-Caen (Flaubert: Revue Critique et Génétique)
Constantly in performance mode, the characters of L’Éducation sentimentale are above all meant to be heard. But their speeches, which are those of Flaubert, knit and unknit communities. Communities based on certain effects of insider understanding and recognition, that call to and stimulate the reader’s critical spirit. Irony is the cause of it, in its own manner, incidental and furtive, central but diffuse. As delicate as it may be, a stylistics of ironic enunciation must thus be undertaken : the present contribution would like to invite to it...